Translating secular-religious divide: everyday negotiation of Christian distinctiveness in Catholic schools in the Czechia and Slovakia - Lukeš Rybanská, Ivana (Journal of beliefs and values, 2022)
The aim of this paper is to inquire into the Christian distinctiveness of church schools as an interactively achieved pragmatic resource. The ethnomethodological perspective incorporated in this research offers an actor- and meaning-focused take on the question of what makes Christian schools different from public schools. We connect this issue to the secular-religious divide debate and argue that church schools in Czechia and Slovakia function as laboratories of secular-religious dialogue. Actors engage in creative translations of Christian values to more secular variations which successfully communicate with the secular public. The interactional approach directed the analysis to the religious, focusing on bordering to create space for the specific identity of the school. The exploration of bordering is based on interviews and ethnographic fieldwork in three Catholic grammar schools in Czechia and Slovakia. This paper shows how unique and divergent enactments of Christian distinctiveness are constructed.